(untitled) (Revista Apotheke, 2022)
The creative process is something constant, configured as a network of connections. In a permanent texture, data is aggregated, creating new records and artistic works interpreted in a poetic. Transcribe the development of three series of works created by me, involving choices, selections and interpretations inherent to the creative continuum. Supported in the process of criticism, I emphasize how this route, in all its personhood, has been delineated in the need to externalize personal conflicts, perceptions and mental elaborations that constitute the human as artist, researcher and professor.